KINERJA PERUSAHAAN SEBAGAI PEMODERASI PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KOMPENSASI EKSEKUTIF - Anggraini, Laila; Fahmi, Muhammad; Espa, Vitriyan (APSSAI ACCOUNTING REVIEW, 2023)
This study aims to determine the impact of company size and leverage on executive compensation with company performance as moderation using quarterly data from Indonesian banking sectors from 2016 to 2021. The data was analyzed using multiple linear and moderated regression analyses (MRA). The results indicate that company size has a positive effect on executive compensation. Meanwhile, leverage proxied by debt to asset (DAR) does not affect executive compensation. In moderation, the results show that return on assets (ROA) and operating expenses towards operating income (BOPO) have succeeded in moderating the impact of company size on executive compensation. Furthermore, while BOPO manages to moderate leverage proxied by DAR on executive compensation, it fails to moderate the relationship between leverage and executive compensation.